1990
DOI: 10.1128/aac.34.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus ventriculitis treated with single-dose intraventricular vancomycin or daptomycin (LY146032): bacterial and antibiotic kinetics in hydrocephalic rabbits

Abstract: Vancomycin and a new antibiotic, daptomycin (LY146032), were tested in vitro and in vivo against Staphylococcus aureus. In vivo tests were performed with rabbits with kaolin-induced hydrocephalus. Five groups of rabbits were studied: untreated ventriculitis, intraventricular vancomycin only, and ventriculitis treated with intraventricular vancomycin (30 ,Ig or 120 jg) or daptomycin (7.5 jig). Results Ventriculitis is a serious complication of shunt placement for hydrocephalus, plaguing 2.7 to 27% of these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It is, therefore, essential that new antimicrobial agents be investigated with reference to their activity against meningitis pathogens. In animal studies of meningitis due to S. aureus (5,7) and Streptococcus pneumoniae (2), daptomycin was more efficacious than vancomycin. However, daptomycin MICs for the S. aureus and S. pneumoniae strains used were 0.25 (7), 1.0 (5), and 0.06 (2), respectively, which are much lower than the daptomycin MIC 50 for L. monocytogenes.…”
mentioning
confidence: 99%
“…It is, therefore, essential that new antimicrobial agents be investigated with reference to their activity against meningitis pathogens. In animal studies of meningitis due to S. aureus (5,7) and Streptococcus pneumoniae (2), daptomycin was more efficacious than vancomycin. However, daptomycin MICs for the S. aureus and S. pneumoniae strains used were 0.25 (7), 1.0 (5), and 0.06 (2), respectively, which are much lower than the daptomycin MIC 50 for L. monocytogenes.…”
mentioning
confidence: 99%
“…5 On the other hand, a study involving a rabbit model of Staphylococcus aureus ventriculitis demonstrated that intraventricular daptomycin achieved greater bactericidal activity, more rapid killing kinetics and a longer half-life in the ventricles than intraventricular vancomycin. 6 Many years' experience of managing patients with EVD-associated ventriculitis by instilling antibiotics into the ventricles encouraged us to treat the patient described in this report with intraventricular daptomycin. This present experience suggests that intraventricular daptomycin is an effective therapy of patients with EVD-associated ventriculitis caused by enterococci; it may be equally appropriate as treatment for patients with ventriculitis caused by other Gram-positive bacteria and those with CSF shunt infections.…”
mentioning
confidence: 99%
“…Daptomycin killed more Staphylococcus aureus more rapidly than vancomycin in this model (Haworth et al 1990). …”
Section: Clinical Usesmentioning
confidence: 93%